Boron Bioaccumulation by the Dominant Macrophytes Grown in Various Discharge Water Environments - Sasmaz, Merve; Senel, Gulsad Uslu; Obek, Erdal (Springer, 2021)
Turkey has the largest boron (B) reserves in the world (> 70 %). Therefore, the land and water resources in Turkey contaminated with high concentration of B Pollution due to mining and industrial operations. This study investigates the accumulation of B in aquatic macrophytes soil and water in the both mining and municipal waste water discharges. For this purpose, soil, plant and water samples were collected from the streams at the areas of mining and municipal waste water discharge sites and analyzed for B using ICP-MS. Results show that the Xanthium strumarium, Eupatorium cannabinum, Lythrum salicaria, Tamarix tetrandra, Typha latifolia, and Salix sp. hyperaccumulate B. These hyperaccumulator plants have a great capacity to accumulate and transport B to plant parts from the soil and water. Therefore, these plants can be useful for decontaminating or rehabilitation of soils and waters polluted with B.
Keywords: Boron; Phytoremediation; Accumulation; Mining and municipal soils; Aquatic macrophytes